PERAN PENGELUARAN PEMERINTAH TERHADAP PENINGKATAN PENDAPATAN PER KAPITA: STUDI KASUS 34 PROVINSI DI INDONESIA - Ruslan, Fadhlurrahman; Ratnawati, Nirdukita; Muliati (Media Ekonomi, 2024)
This study aims to see the effect of government spending on income per capita of 34 provinces in Indonesia. This study uses panel data regression (pooled data) to determine the effect of government spyending, namely education function, health function, and social assistance, on the dependent variable income per capita. The data used secondary data of 34 provinces in Indonesia over the period 2016-2020 published by the Ministry of Finance and Central Statistics Agency. The result showed that government spending on education and public service functions with 5% error rate are statistically significant have sign in accordance with expectation, then H1 and H4 are accepted. While spending on social function has reversed sign and health function has no influence on income per capita of 34 provinces in Indonesia for 2015-2019 period